Kapitał ludzki i kapitał społeczny a dobrobyt materialny. Polski paradoks - Czapiński, Janusz (Journal of Public Governance, 2008)
Human capital is the main prerequisite of success in competition between individuals. Social capital is a factor responsible for development of the whole society with a relatively high level of human capital. During the period of transformation Poles has been investing a lot in human capital (education and health). However, social capital stayed in this time at the very low, the lowest in Europe level. This means that human capital was the main source of Polish economic development during the last 20 years. Without significant investment in social capital further development can be remarkably slowed down.